2017
DOI: 10.3389/fphys.2017.00441
|View full text |Cite
|
Sign up to set email alerts
|

4D Flow Analysis of BAV-Related Fluid-Dynamic Alterations: Evidences of Wall Shear Stress Alterations in Absence of Clinically-Relevant Aortic Anatomical Remodeling

Abstract: Bicuspid aortic valve (BAV) is the most common congenital cardiac disease and is a foremost risk factor for aortopathies. Despite the genetic basis of BAV and of the associated aortopathies, BAV-related alterations in aortic fluid-dynamics, and particularly in wall shear stresses (WSSs), likely play a role in the progression of aortopathy, and may contribute to its pathogenesis. To test whether WSS may trigger aortopathy, in this study we used 4D Flow sequences of phase-contrast cardiac magnetic resonance imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 46 publications
(79 reference statements)
5
68
0
Order By: Relevance
“…Similar findings are present in computational (Bonomi et al 2015) and in vivo studies (Mahadevia et al 2014;Bissell et al 2013), where higher degrees of ascending aortic dilation were associated with lower WSS values. Nonetheless, previous 4D flow studies using nondilated aortas have suggested that abnormally high WSS may anticipate the onset of aortopathy and contribute to its triggering (Piatti et al 2017).…”
Section: Does Aortic Dilation Have An Impact On Bav Flow Abnormalities?mentioning
confidence: 95%
“…Similar findings are present in computational (Bonomi et al 2015) and in vivo studies (Mahadevia et al 2014;Bissell et al 2013), where higher degrees of ascending aortic dilation were associated with lower WSS values. Nonetheless, previous 4D flow studies using nondilated aortas have suggested that abnormally high WSS may anticipate the onset of aortopathy and contribute to its triggering (Piatti et al 2017).…”
Section: Does Aortic Dilation Have An Impact On Bav Flow Abnormalities?mentioning
confidence: 95%
“…Current methods either solely rely on manual segmentation, which comes with implicit user biases and inaccuracies, or with semiautomated methods which expedite the process by averaging frames and/or using splines. [5][6][7][8][9][10][11][12][13][14][15][16][17] While efficient, use of splines is sensitive to a variety of hyperparameters such as the specific position of the nodes. 8 Our proposed algorithm relies solely on empirical data to classify voxels as edge or lumen and is, therefore, both userindependent and inherently reproducible.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12] In the second approach, trained observers use semiautomatic segmentation packages and interpolation to generate a 3D mesh of the aorta and subsequently evaluate WSS. [13][14][15][16][17] While these are viable methods for calculating WSS on a case-by-case basis, multiple authors note that their primary limitation is the need for user-input for manual segmentation of the aorta. [5][6][7][13][14][15] Specifically, manual segmentation can lead to inter-observer variability for the lumen boundary as well as potential inaccuracies due to the spatiotemporal interpolations involved in 3D mesh generation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations